Disambiguating ambiguous motion perception: what are the cues? - Piedimonte, Alessandro; Woods, Adam J.; Chatterjee, Anjan (Frontiers in Psychology, 2015)
Motion perception is a fundamental feature of the human visual system. As part of our daily life we often have to determine the direction of motion, even in ambiguous situations. These situations force us to rely on exogenous cues, such as other environmental motion, endogenous cues, such as our own actions, or previously learned experiences. In three experiments, we asked participants to report the direction of an ambiguous motion display, manipulating exogenous and endogenous sources of information. Specifically, in all three experments the exogenous information was represented by another motion cue while the endogenous cue was represented respectively by movement execution, movement planning, or a learned association about the motion display. Participants were consistently biased by stable motion cues in the environment when reporting the ambiguous target direction. In the absence of stable exogenous motion information, participants were biased by their motor movements and even the planning of such movements. However, when participants learned a specific association about the target motion, this acquired endogenous knowledge countered exogenous motion cues in biasing participants’ perception. Taken together, our findings demonstrate that we disambiguate ambiguous motion using different sources of exogenous and endogenous cues, and that learned associations may be particularly salient in countering the biasing effects of environmental cues.